Agricultural output and government expenditure in Nigeria - KEJI Sunday Anderu; EFUNTADE Olubunmi Omotayo (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
The study empirically investigate the link between agricultural output growth and government spending in Nigeria from 1981 to 2018. Augmented Dickey-Fuller (ADF) test was used to investigate stationary variable at different levels. The mixture in order of integration necessitate Auto Redistributed Lag (ARDL) and Bounds co-integration, since it allows combination of fractionally integrated variables. The results show both short and long run effect of government spending on the growth of agricultural output in Nigeria. The policy implication is that any disruption in government spending on agricultural sector would have adverse effect on agricultural output growth in Nigeria. In view of poor agricultural output growth in Nigeria, coupled with corruption, and policy summersaults in the sector. It is pertinent in the study, to come up with the following recommendations thus; government should re-double it efforts in terms food security through improved agricultural policies, proper channelization of loans across board with sustainable fiscal measures that can translate to actual growth.